2001
DOI: 10.1046/j.1365-2044.2001.01422-2.x
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the conus medullaris following spinal anaesthesia

Abstract: SummaryNon-invasive positive pressure ventilation has previously been used successfully to treat both acute and chronic ventilatory failure secondary to a number of conditions, including scoliosis. We report two patients in whom it was used, on three separate occasions, to treat acute ventilatory failure following corrective spinal surgery. Non-invasive positive pressure ventilation may be useful postoperatively in high-risk patients undergoing major spinal surgery in an attempt to prevent intubation and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
1
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(164 citation statements)
references
References 36 publications
(43 reference statements)
5
151
1
7
Order By: Relevance
“…Recently, two case series from Great Britain documented spinal cord trauma after spinal or combined spinal/epidural anesthesia. 13,14 In one study, the level of puncture recorded on the anesthetic record was two or three segments lower than the subsequent damage as shown by MRI. Of note, no patient's conus medullaris was situated below L1.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, two case series from Great Britain documented spinal cord trauma after spinal or combined spinal/epidural anesthesia. 13,14 In one study, the level of puncture recorded on the anesthetic record was two or three segments lower than the subsequent damage as shown by MRI. Of note, no patient's conus medullaris was situated below L1.…”
Section: Discussionmentioning
confidence: 96%
“…A high frequency (7)(8)(9)(10)(11)(12)(13)(14)(15) MHz) linear transducer is preferred for peripheral nerve blocks and central venous cannulations where the structures to be visualized are located superficially. This transducer produces a high-resolution image; however, it has poor beam penetration.…”
Section: Basic Concepts Of Spinal Ultrasoundmentioning
confidence: 99%
“…It is important to identify levels accurately and to choose a level below conus medullaris during spinal anesthesia to prevent spinal cord trauma. 11 Broadbent et al demonstrated that even experienced anesthesiologists estimate the intervertebral level inaccurately by palpation in 71% of cases; they tend to estimate the level as higher than the actual, and their estimate could be as many as four spaces higher. 12 Tuffier's line, an anatomical landmark widely used for this purpose, does not always bear a constant relationship to an individual vertebral level or the interspace.…”
Section: Efficacy Of Ultrasound-guided Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients referred pain at needle insertion or local anesthetic injection. In all cases, pencil point bevel needles were used (Whitacre) and puncture was performed in L 2 -L 3 or L 1 -L 2 interspace 14 . When pencil point needles are used, it is necessary to further introduce it in the spinal space to obtain cerebral spinal fluid (CSF).…”
Section: Needle or Catheter-induced Nerve Injurymentioning
confidence: 99%